The winter ghosts [compact disc, unabridged] - Mosse, Kate, 1961- (Penguin Audio, 2011)
In the winter of 1928, still seeking some kind of resolution to the horrors of World War I, Freddie is traveling through the beautiful but forbidding French Pyrenees. During a snowstorm, his car spins off the mountain road. Dazed, he stumbles through the woods, emerging in a tiny village, where he finds an inn to wait out the blizzard. There he meets Fabrissa, a lovely young woman also mourning a lost generation. Over the course of one night, Fabrissa and Freddie share their stories.